Kajian Ulang Nisab Zakat Emas Dalam Qanun Aceh Nomor 3 Tahun 2021 - Tampubolon, Mulkan Tarida Tua (Institut Syekh Abdul Halim Hasan Binjai, 2024)
This article aims to conduct a reevaluation of the Gold Zakat Nisab within the Aceh Qanun No. 3 of 2021. The Gold Zakat Nisab is the focal point of this study due to its relevance in determining the amount of zakat that must be paid by individuals or communities who possess gold wealth above a certain threshold. Through an analytical approach to the implementation of these regulations, this article evaluates their relevance, fairness, and effectiveness within the economic and social context of Acehnese society. By discussing the historical background of gold zakat regulation in Islamic law, reviewing the provisions of the Gold Zakat Nisab within the Aceh Qanun, analyzing the implementation of these regulations, and proposing potential improvements or refinements, this article aims to make a positive contribution to the development of better zakat policies in Aceh. Additionally, it aims to contribute to the academic literature on Islamic economics.